Changes In The Digestibility Coefficient At Different Stages Of Ontogenesis - Xujanova Latofat Absalomovna; Babamuratova Hanifa Iranovna; Mirazimova Xafiza; Ruziyeva Munavvar (Stanford Database Library of American Journal of Applied Science and Technology, 2026)
The article discusses the importance of correctly determining the nutritional value of food products when assessing the digestibility coefficient in humans. It also presents information on the reasons for age- and sex-related variations in this indicator and on factors that can enhance digestibility.